2020
DOI: 10.1177/1060028020912429
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Resuming Direct Oral Anticoagulant Therapy Following Admission for a Gastrointestinal Bleed

Abstract: Background: Although direct oral anticoagulants (DOACs) carry a lower bleeding risk compared with warfarin, gastrointestinal bleeds (GIB) are a known complication. There are limited data observing outcomes associated with resuming DOACs following a GIB. Objective: The purpose of this study was to evaluate practice patterns and clinical outcomes of patients admitted with an index GIB while receiving DOAC therapy. Methods: This retrospective, single-system study included adult patients receiving DOAC therapy pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“… 12 There was a 3% increase in patients who experienced a recurrent GIB after the resumption of DOACs. 12 , 27 Proietti et al focused on dabigatran and found that patients who were started on dabigatran had a reduced risk for recurrent GIB compared to those who started on warfarin. 18 Smit and Gelder reported that 49% of dabigatran users restarted anticoagulation after significant bleeding, and the risk of ischemic stroke and all-cause mortality decreased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 12 There was a 3% increase in patients who experienced a recurrent GIB after the resumption of DOACs. 12 , 27 Proietti et al focused on dabigatran and found that patients who were started on dabigatran had a reduced risk for recurrent GIB compared to those who started on warfarin. 18 Smit and Gelder reported that 49% of dabigatran users restarted anticoagulation after significant bleeding, and the risk of ischemic stroke and all-cause mortality decreased.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Other studies, however, have reported recurrent GIB issues associated with rivaroxaban. 17 , 27 , 30 Valanejad et al demonstrated that rivaroxaban was the only DOAC that increased the risk of recurrent GIB. 27 Overall, most research reports that the resumption of DOACs reduces the risk of thromboembolism and all-cause mortality with a selective increase in recurrent GIBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High quality prospective studies should be prioritized to get direct data from patients. Two systematic reviews showed survival advantage after anticoagulant resumption, no RCT or prospective study has been published, but six retrospective studies were found [33][34][35][36][37][38]. Anticoagulant resumption increased the rate of GI bleeding and decreased the rate of thromboembolism, with a net benefit on mortality [38].…”
Section: When Can Anticoagulant Medication Be Restarted Following Gastrointestinal Bleeding?mentioning
confidence: 99%